An investigation of the relationship of beliefs, values and technological pedagogical content knowledge among teachers. Issue 4 (8th August 2018) - Lai, Ting-ling; Lin, Hsiao-Fang
ABSTRACT: The purpose of this study was to investigate the relationship among student-centred beliefs, technology value beliefs and technological pedagogical content knowledge (TPACK) in junior high school mathematics teachers. A survey was administered to 408 teachers in Taiwan. Regression analysis results showed that teachers' student-centred beliefs and technology values were significantly correlated with TPACK. MANOVA results found that teachers with high student-centred pedagogical beliefs may not have high technology values, and teachers with lower student-centred pedagogical beliefs may not have lower TPACK. Implications for professional development and suggestions regarding teachers' beliefs and TPACK are discussed.